Delirium Management Quality Improvement Project to Improve Awareness and Screening in a Medical ICU - Hirsh Makhija; Kyle Digrande; Omar Awan; Russell G. Buhr; Rajan Saggar; Victoria Ramirez; Rainbow Tarumoto; Janelle M. Fine; Atul Malhotra; Dale M. Needham; Jennifer L. Martin; Biren B. Kamdar (Nursing Reports)
Background/Objectives: Although delirium is common during critical illness, standard-of-care detection and prevention practices in real-world intensive care unit (ICU) settings remain inconsistent, often due to a lack of provider education. Despite availability for over 20 years of validated delirium screening tools such as the Confusion Assessment Method in the ICU (CAM-ICU), feasible and rigorous educational efforts continue to be needed to address persistent delirium standard-of-care practice gaps. Methods: Spanning an 8-month quality improvement project period, our single-ICU interdisciplinary effort involved delivery of CAM-ICU pocket cards to bedside nurses, and lectures by experienced champions that included a live delirium detection demonstration using the CAM-ICU, and a comprehensive discussion of evidence-based delirium prevention strategies (e.g., benzodiazepine avoidance). Subsequent engagement by health system leadership motivated the development of an electronic health record dataset to evaluate unit-level outcomes, including CAM-ICU documentation and benzodiazepine administration. Results: Using a dataset that spanned 9 pre- and 37 post-project months and included 3612 patients, 4470 admissions, and 33,913 patient days, we observed that delirium education was followed by a dramatic rise in CAM-ICU documentation, from <1% for daytime and nighttime shifts to peaks of 73% and 71%, respectively (p < 0.0001 for trend), and a fall in the proportion of mechanically ventilated patients ever receiving benzodiazepine infusions (69% to 41%; p < 0.0001). Conclusions: An interdisciplinary delirium project comprising rigorous lectures on standard-of-care practices can yield significant improvements in documentation and sedative administration. This approach can help ICUs jumpstart efforts to build awareness and address longstanding gaps in standard-of-care delirium practices.